Cucurbitacin IIb from Ibervillea sonorae Induces Apoptosis and Cell Cycle Arrest via STAT3 Inhibition - Torres-Moreno, Heriberto; Marcotullio, Maria C.; Velazquez, Carlos; Arenas-Luna, Víctor M.; Hernández-Gutiérrez, Salomón; Robles-Zepeda, Ramón E. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Cucurbitacin IIb (CIIb) from Ibervillea sonorae has a high capacity to suppress cancer cell proliferation and induce apoptosis. This study investigated the molecular mechanisms related to the antiproliferative and apoptosis induction capacity of CIIb in HeLa cells. Materials and Methods: The cell viability and anti-proliferative effect of CIIb were evaluated by using the trypan blue exclusion assay. The effect of CIIb on the mitochondrial membrane potential was determined by flow cytometry using JC-1. The activity of caspase-3 and caspase-9 was evaluated by flow cytometry using commercial kits. The effect of CIIb on the cell cycle was investigated using Fluorescence-Activated Cell Sorting (FACS) analysis. Western blot analysis was used to evaluate both the inhibitory effect of CIIb on the STAT3 signaling pathway and cyclin –B1, and DNA damage by the comet assay. Results: CIIb triggers disruption of the mitochondrial membrane potential (Δψm) and consequently activated the caspases -3 and -9, as a result of the activation of the intrinsic pathway of the apoptosis. Likewise, the CIIbinduced cell cycle was arrested in S and G2/M after 24h of treatment. CIIb also reduced the expression of STAT3 and cyclin –B1. Finally, CIIb produced an antiproliferative effect at 48 and 72 h, inducing DNA damage. Conclusion: These results demonstrate CIIb-induced apoptosis and cell cycle arrest in HeLa through the inhibition of STAT3.
Keywords: mitochondrial membrane potential